Review of Ioannis D. Evrigenis' Αντίπαλον δέος: Έξωθεν φόβος και συλλογική δράση [Fear of Enemies and Collective Action] - Steiris, Georgios (Historein, 2015)
Review of Ioannis D. Evrigenis, Αντίπαλον δέος: Έξωθεν φόβος και συλλογική δράση [Fear of Enemies and Collective Action], Iraklio: Crete University Press, 2014. 448 pp.